Hydrogenation catalyst, preparation method and application thereof, and method for catalyzing hydrofining of diesel oil
By developing a catalyst containing hydrogenation active components and support, the problems of poor denitrification effect and low monocyclic aromatic hydrocarbon content during catalytic diesel hydrogenation are solved, and efficient denitrification and high selectivity monocyclic aromatic hydrocarbon generation are achieved, meeting the needs of high value-added utilization.
Patent Information
- Application Number
- CN202311145995.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-09-06
AI Technical Summary
The prior art has poor nitrogen removal effect during catalytic diesel hydrogenation process, and the monocyclic aromatic hydrocarbon content is low, making it difficult to meet the demand for high value-added utilization.
A catalyst containing a hydrogenation active component and a support is developed, which contains alkaline earth metals. The hydrogenation active component is composed of Group VIII and Group VIB elements and has a layered stacking structure. Through a specific preparation method, the catalyst adjusts the acid properties of the support surface, reduces the interaction strength between the active metal and the support, and improves the dispersion of the active components.
It achieves excellent nitrogen removal effect and high monocyclic aromatic hydrocarbon selectivity in catalytic diesel hydrocarbons, and improves the quality and added value of the product.
Smart Images

Figure CN119588372A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalytic diesel hydrofining, and in particular to a hydrogenation catalyst and a preparation method and application thereof, and a method for catalytic diesel hydrofining. Background Art
[0002] Catalytic cracking diesel (also known as light cycle oil, catalytic diesel, LCO) is a heavy diesel fraction produced from a catalytic cracking (FCC) unit. It has a complex composition and an aromatic content of up to 80%, of which naphthalene-based bicyclic aromatics account for about 70%, monocyclic aromatics and tricyclic aromatics account for about 15% each, and the rest are small amounts of alkanes, cycloalkanes and olefins. The sulfur content in LCO is about 0.2-1.5wt%, the nitrogen content is about 100-1000ppm, the cetane number is 15-25, the ignition performance is poor, and it cannot be directly used as automotive diesel. With the squeeze-out effect of oil pool saturation and shrinking diesel consumption, LCO utilization has become a serious problem facing oil refining companies, restricting the full-load operation of corporate units and the improvement of overall benefits.
[0003] At present, LCO processing methods usually adopt hydrofining and hydrocracking. The functions of hydrofining are mainly desulfurization, denitrogenation and aromatic saturation reaction. Hydrofining can improve its color and stability, but the cetane number is only slightly improved and cannot reach the cetane number index of automotive diesel. The hydrocracking process, such as UOP's Unicracking process, can produce gasoline, jet fuel and diesel products, but when the proportion of secondary processed oil such as LCO is too high, qualified jet fuel products cannot be obtained. In view of the characteristics of LCO rich in aromatics, in order to achieve its high added value utilization, UOP has developed the LCO-X process, which is a new process for producing xylene and benzene through hydroconversion-selective alkyl transfer. The process principle is that LCO is first hydrofined to remove sulfur and nitrogen impurities in the raw oil, and the polycyclic aromatics therein are selectively hydrogenated and saturated, and then enters the hydrocracking reactor for selective cracking reaction. In the LCO-X process, the total yield of xylene + benzene is about 44%. In addition, some liquefied gas, light naphtha and ultra-low sulfur diesel components are also produced as by-products. This process requires the construction of a series of reaction and separation units after the hydrocracking reaction. The process is long and the investment is high. There are no reports on its industrial application.
[0004] In view of the current problems of oil upgrading and gasoline / diesel pool saturation, chemical conversion has become an inevitable trend for LCO utilization. The most competitive chemical utilization route is to produce light aromatics and low-carbon saturated hydrocarbons through two-stage reactions of LCO hydrofining and hydrocracking. Light aromatics can be directly fed into the aromatics joint unit, and low-carbon saturated hydrocarbons can be used as raw materials for steam cracking to produce ethylene, thereby realizing the high added value of LCO. In the two-stage process, in order to achieve a high aromatic yield, the first-stage hydrofining process should have the following characteristics: 1. High conversion rate of concentrated ring aromatics to maximize the production of single-ring aromatics; 2. High single-ring aromatics selectivity to avoid aromatics loss caused by deep hydrogenation; 3. Deep desulfurization and denitrogenation performance, thereby providing high-quality raw materials for the second-stage hydrocracking. Deep denitrogenation requires the strengthening of hydrogenation function, while increasing the aromatic content requires the suppression of deep hydrogenation. Therefore, to meet the above requirements at the same time, it poses a very great challenge to the development of hydrofining catalysts.
[0005] CN105754646A The invention discloses a combined method of catalytic cracking diesel hydrogenation conversion and catalytic gasoline hydrogenation
[0006] CN1040610A discloses a hydrogenation refining catalyst with γ-A12O3 containing TiO2 as a carrier, wherein the content of titanium oxide in the carrier catalyst γ-A12O3 is 5-30%, and W, Mo, and Ni are active components. The performance of the hydrogenation catalyst with TiO2-modified A12O3 as a carrier will be improved to a certain extent, and the acid content of the carrier is low, especially the medium-strong acid center is less, which is not conducive to the ring-opening and breaking of the nitrogen heterocycle, and the denitrification effect is not obvious.
[0007] In the petroleum hydrocarbon hydroprocessing method disclosed in USP4880524, a highly active hydrogenation catalyst is used. The catalyst is of NiMo / A12O3 type with a specific surface area greater than 300m 2 / g, and the pore size less than 7nm is greater than 70%. The catalyst has good hydrofining activity for light distillate oil, but has poor hydrofining effect for catalytic diesel fraction with relatively large molecular size.
[0008] CN109777514A discloses a method for catalytic diesel hydrogenation conversion to aromatics, which adopts a two-stage hydrorefining + hydrocracking process. The hydrorefining catalyst has high acid strength, the aromatics yield in the refining process is low, and the aromatics loss is large. It can be used as a catalytic diesel oil product solution, but is not suitable for chemical use of catalytic diesel. Summary of the invention
[0009] The purpose of the present invention is to overcome the problems of poor catalytic diesel hydrodenitrogenation effect and low content of monocyclic aromatic hydrocarbons in the product in the prior art, and to provide a hydrogenation catalyst and its preparation method and application and a method for catalytic diesel hydrorefining, wherein the catalyst has excellent denitrogenation effect and monocyclic aromatic hydrocarbon selectivity.
[0010] In order to achieve the above objectives, the first aspect of the present invention provides a hydrogenation catalyst, which comprises a hydrogenation active component and a carrier, wherein the carrier comprises an alkaline earth metal, and the hydrogenation active component comprises a Group VIII element and a Group VIB element; the hydrogenation active component has a layered stacking structure.
[0011] The second aspect of the present invention provides a method for preparing the hydrogenation catalyst according to the first aspect, the preparation method comprising:
[0012] a. first mixing the carrier, the alkaline earth metal, the first additive and optionally the organic acid in a first solvent, first drying and first calcining to obtain an intermediate product;
[0013] b. mixing the intermediate product with a hydrogenation active component precursor and a second additive in a second solvent, performing a second drying and a second calcination to obtain a hydrogenation catalyst;
[0014] The first additive is a nonionic surfactant; the second additive is a polybasic inorganic acid or a polybasic organic acid.
[0015] The third aspect of the present invention provides an application of the hydrogenation catalyst described in the first aspect.
[0016] A fourth aspect of the present invention provides a method for catalytic diesel hydrorefining, the method comprising contacting the catalytic diesel with hydrogen in the presence of a catalyst to carry out a hydrogenation reaction; the catalyst is the presulfurized hydrogenation catalyst of the first aspect.
[0017] Through the above technical solution, the present invention has the following advantages:
[0018] The catalyst of the present invention comprises a hydrogenation active component and a carrier, wherein the carrier comprises an alkaline earth metal, which can adjust the acid properties of the carrier surface and reduce the interaction strength between the hydrogenation active metal and the carrier. The catalyst of the present invention having a layered stacking structure of the hydrogenation active component obtained by the preparation method of the present invention has a technical effect of improving the dispersion of the active component.
[0019] The catalyst of the invention is applied to catalytic diesel hydrofining and has excellent denitrification effect and monocyclic aromatic hydrocarbon selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a transmission electron microscope (TEM) image of the catalyst of Example 1;
[0021] Figure 2 is the ammonia temperature programmed desorption (NH3-TPD) curve of the catalyst in Example 1;
[0022] Figure 3 is a TEM image of the catalyst of Example 2;
[0023] Figure 4 This is a TEM image of the catalyst of Comparative Example 1. DETAILED DESCRIPTION
[0024] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0025] The present invention provides a hydrogenation catalyst, which comprises a hydrogenation active component and a carrier, wherein the carrier comprises an alkaline earth metal, and the hydrogenation active component comprises a Group VIII element and a Group VIB element; the hydrogenation active component is in a layered stacking structure.
[0026] The catalyst of the present invention comprises hydrogenation active components of Group VIII elements and Group VIB elements and a carrier, wherein the carrier comprises an alkaline earth metal, which can adjust the acid properties of the carrier surface and reduce the interaction strength between the hydrogenation active metal and the carrier. The catalyst of the present invention having a layered stacking structure of hydrogenation active components obtained by the preparation method of the present invention has a technical effect of improving the dispersion of the active components.
[0027] According to a preferred embodiment of the present invention, the active components of the hydrogenation catalyst are in a layered stacking structure of 3-10 layers, preferably, the active components of the hydrogenation catalyst are in a layered stacking structure of 3-7 layers.
[0028] According to a preferred embodiment of the present invention, the stacking length of each layer in the stacking structure of the active components of the hydrogenation catalyst is 3-25nm, for example, it can be 3-7nm, 3-15nm, 5-15nm, 5-25nm, 6-12nm, 6-18nm, 6-25nm; preferably, the stacking length of each layer is 3-7nm.
[0029] In the present invention, the optional range of the types of the carrier is relatively wide. According to a preferred embodiment of the present invention, the carrier is selected from at least one of silicon aluminum molecular sieve, phosphorus aluminum molecular sieve, silicon dioxide, zirconium dioxide, titanium dioxide, and aluminum oxide.
[0030] According to a preferred embodiment of the present invention, the carrier contains 0.1-1.0 wt % of alkaline earth metal.
[0031] In the present invention, alkaline earth metals are suitable for the present invention. According to a preferred embodiment of the present invention, the alkaline earth metal is selected from at least one of Mg, Ca, Sr and Ba, and more preferably Ca. By adopting the above preferred embodiment, the hydrogenation performance of the equilibrium catalyst can be further improved, and the denitrification effect and the selectivity of monocyclic aromatic hydrocarbons can be improved.
[0032] According to a preferred embodiment of the present invention, the specific surface area of the hydrogenation catalyst is 150-300m 2 / g, preferably 180-300m 2 / g.
[0033] According to a preferred embodiment of the present invention, the average pore diameter of the hydrogenation catalyst is 10-20 nm, preferably 10-15 nm.
[0034] According to a preferred embodiment of the present invention, the pore volume of the hydrogenation catalyst is 0.7-1.3 ml / g, preferably 0.85-1.2 ml / g.
[0035] According to a preferred embodiment of the present invention, the surface of the hydrogenation catalyst has suitable acid properties, and the density ratio of weak acid sites to medium and strong acid sites is about 2-4:1.
[0036] In the present invention, there is no particular restriction on the content of each component in the hydrogenation catalyst. According to a preferred embodiment of the present invention, in the hydrogenation catalyst, the carrier content is 50-85%, preferably 75-85%, by weight percentage; the hydrogenation active component content is 15-50%, preferably 15-25%, calculated as metal oxide. By adopting the above preferred scheme, the hydrogenation performance of the balanced catalyst can be further improved, and the denitrification effect and the selectivity of monocyclic aromatic hydrocarbons can be improved.
[0037] In the present invention, as long as the purpose of the present invention can be achieved, there is no particular restriction on the mass ratio of the Group VIII element to the Group VIB element in the hydrogenation active component. According to a preferred embodiment of the present invention, the mass ratio of the Group VIII element to the Group VIB element in the hydrogenation active component measured in terms of metal oxide is 0.1-0.5. By adopting the above preferred scheme, the hydrogenation performance of the equilibrium catalyst can be further improved, and the denitrification effect and the selectivity of monocyclic aromatic hydrocarbons can be improved.
[0038] According to a preferred embodiment of the present invention, the Group VIII element is selected from at least one of Fe, Co and Ni, preferably Ni and / or Co.
[0039] According to a preferred embodiment of the present invention, the Group VIB element is selected from at least one of Cr, Mo and W, preferably Mo and / or W.
[0040] The present invention provides a method for preparing the hydrogenation catalyst of the present invention, the preparation method comprising:
[0041] a. first mixing the carrier, the alkaline earth metal, the first additive and optionally the organic acid in a first solvent, first drying and first calcining to obtain an intermediate product;
[0042] b. mixing the intermediate product with a hydrogenation active component precursor and a second additive in a second solvent, performing a second drying and a second calcination to obtain a hydrogenation catalyst;
[0043] The first additive is a nonionic surfactant; the second additive is a polybasic inorganic acid or a polybasic organic acid.
[0044] By adopting the above-mentioned preparation method, the catalyst having the characteristics of the present invention can be prepared.
[0045] According to a preferred embodiment of the present invention, the first additive is selected from polyethylene glycol and / or Tween; the second additive is a polybasic inorganic acid.
[0046] According to a preferred embodiment of the present invention, the first additive is polyethylene glycol 200; the second additive is phosphoric acid.
[0047] According to a preferred embodiment of the present invention, the first mixing and the second mixing modes are independently selected from equal volume impregnation and / or excess impregnation, preferably equal volume impregnation.
[0048] According to a preferred embodiment of the present invention, the hydrogenation active component precursor is a compound corresponding to the Group VIII element and / or the Group VIB element, preferably a corresponding salt.
[0049] In the present invention, the preparation of the carrier can be a conventional method in the art. According to a preferred embodiment of the present invention, the preparation method of the carrier comprises: mixing a carrier precursor, an extrusion aid and a peptizing acid to obtain a carrier. By adopting the above preferred scheme, the hydrogenation performance of the equilibrium catalyst can be further improved, and the denitrification effect and the selectivity of monocyclic aromatic hydrocarbons can be improved.
[0050] According to a preferred embodiment of the present invention, the carrier is obtained by drying and calcining after molding, preferably by drying at 100-120° C. for 4-8 hours and then calcining at 600-800° C. for 4-8 hours.
[0051] According to a preferred embodiment of the present invention, the extrusion aid is selected from at least one of sesbania powder, polyvinyl alcohol and hydroxymethyl cellulose.
[0052] According to a preferred embodiment of the present invention, the extrusion aid is polyvinyl alcohol, and the mass concentration of the polyvinyl alcohol solution is preferably 1-10%.
[0053] According to a preferred embodiment of the present invention, the peptizing acid is selected from one or more of phosphoric acid, nitric acid and acetic acid, preferably a mixed solution of nitric acid and phosphoric acid, more preferably the volume ratio of nitric acid to phosphoric acid in the mixed solution is 1-2:2-1.
[0054] According to a preferred embodiment of the present invention, the molding includes forming into a clover bar shape, a cylindrical bar shape, and a spherical shape, preferably a clover bar shape.
[0055] In the present invention, as long as the purpose of the present invention can be achieved, there is no particular restriction on the weight ratio of the carrier, alkaline earth metal, first additive and organic acid in step a. According to a preferred embodiment of the present invention, in step a, the weight ratio of the carrier, alkaline earth metal in terms of oxide, first additive and organic acid is 1: 0.01-0.04: 0.02-0.05: 0.05-0.15. By adopting the above preferred scheme, the hydrogenation performance of the equilibrium catalyst can be further improved, and the denitrification effect and the selectivity of monocyclic aromatic hydrocarbons can be improved.
[0056] According to a preferred embodiment of the present invention, the organic acid is selected from at least one of citric acid, tartaric acid and oxalic acid.
[0057] According to a preferred embodiment of the present invention, the first solvent is selected from at least one of deionized water, ethanol, and acetic acid / sodium acetate buffer solution.
[0058] According to a preferred embodiment of the present invention, the second solvent is selected from at least one of deionized water, ethanol, and acetic acid / sodium acetate buffer solution.
[0059] According to a preferred embodiment of the present invention, the first drying conditions include: a drying temperature of 60° C.-150° C., and a drying time of 2 h-24 h.
[0060] According to a preferred embodiment of the present invention, the first calcination conditions include: a calcination temperature of 250° C.-750° C., and a calcination time of 2 h-12 h.
[0061] According to a preferred embodiment of the present invention, the second drying conditions include: drying temperature of 60° C.-150° C., and drying time of 2 h-24 h.
[0062] According to a preferred embodiment of the present invention, the second calcination conditions include: a calcination temperature of 250° C.-750° C., and a calcination time of 2 h-12 h.
[0063] The present invention provides an application of the catalyst of the present invention in catalytic diesel hydrorefining.
[0064] The catalyst of the invention is applied to catalytic diesel hydrofining and has excellent denitrification effect and monocyclic aromatic hydrocarbon selectivity.
[0065] The present invention provides a method for catalytic diesel hydrofining, which comprises contacting catalytic diesel with hydrogen in the presence of a catalyst to carry out a hydrogenation reaction, wherein the catalyst is a presulfurized hydrogenation catalyst of the present invention.
[0066] By adopting the method of the present invention to carry out catalytic diesel hydrorefining, the denitrogenation rate and monocyclic aromatic hydrocarbon selectivity of the refined product are high.
[0067] According to a preferred embodiment of the present invention, the distillation range of the catalytic diesel is 200-370° C., preferably 200-330° C. By adopting the above preferred scheme, the denitrification rate and monocyclic aromatic hydrocarbon selectivity of the refined product can be further improved.
[0068] According to a preferred embodiment of the present invention, the density of the catalytic diesel is above 0.90 g / ml, preferably above 0.93 g / ml. By adopting the above preferred scheme, the denitrification rate and monocyclic aromatic hydrocarbon selectivity of the refined product can be further improved.
[0069] According to a preferred embodiment of the present invention, the catalytic diesel is from a DCC and / or MIP process.
[0070] According to a preferred embodiment of the present invention, the catalytic diesel contains, by weight percentage, 15-25% monocyclic aromatic hydrocarbons, 50-60% dicyclic aromatic hydrocarbons, 2-8% tricyclic aromatic hydrocarbons; and 7%-33% other components, preferably other components include saturated hydrocarbons such as paraffins and cycloalkanes. By adopting the above preferred scheme, the denitrification rate of the refined product and the selectivity of monocyclic aromatic hydrocarbons can be further improved.
[0071] According to a preferred embodiment of the present invention, the conditions of the hydrogenation reaction include: reaction temperature 260-320°C, preferably 270-300°C; reaction pressure 5.0-8.0MPa, preferably 6.0-7.0MPa; volume space velocity 0.6-1.0h -1 , preferably 0.7-0.8h -1 ; Hydrogen to oil volume ratio is 1000-2000, preferably 1200-1500. By adopting the above preferred scheme, the denitrogenation rate and monocyclic aromatic hydrocarbon selectivity of the refined product can be further improved.
[0072] According to a preferred embodiment of the present invention, the pre-sulfurization conditions include: under the conditions of hydrogen partial pressure of 4-6MPa and hydrogen sulfide concentration of 5000-15000ppm in circulating hydrogen, the temperature is raised according to the program and the sulfidation is carried out at 210-250°C for 12-20h, 260-300°C for 12-20h and 310-340°C for 12-20h respectively; the total sulfidation time is 36-60h.
[0073] The present invention will be described in detail below through examples.
[0074] In the following embodiments:
[0075] Conversion rate of dicyclic aromatic hydrocarbons (%) = (content of dicyclic aromatic hydrocarbons in raw materials × content of dicyclic aromatic hydrocarbons in products) / content of dicyclic aromatic hydrocarbons in raw materials × 100%;
[0076] Conversion rate of tricyclic aromatic hydrocarbons (%) = (content of tricyclic aromatic hydrocarbons in raw materials × content of tricyclic aromatic hydrocarbons in products) / content of tricyclic aromatic hydrocarbons in raw materials × 100%;
[0077] Selectivity of monocyclic aromatic hydrocarbons (%) = (content of monocyclic aromatic hydrocarbons in the product / content of monocyclic aromatic hydrocarbons in the raw material) / (content of polycyclic aromatic hydrocarbons in the raw material / content of polycyclic aromatic hydrocarbons in the product) × 100%;
[0078] Denitrification rate (%) = (nitrogen-containing compound content in raw materials - nitrogen-containing compound content in products) / nitrogen-containing compound content in raw materials × 100%.
[0079] Example 1
[0080] 1. Catalyst preparation
[0081] Weigh 20 g of pseudo-boehmite equivalent to aluminum oxide, 130 g of aluminum oxide, and 8 g of sesbania powder, mix them, then add 20 g of polyvinyl alcohol solution (mass concentration of 5%), 2.4 g of 85% phosphoric acid, 3.2 g of 67% nitric acid, and 200 ml of water, and squeeze into The millimeter clover strips were dried at 110°C for 6 hours and then calcined at 700°C for 6 hours to obtain a carrier. 50 grams of the sample obtained by the calcination was impregnated and mixed with a mixed aqueous solution containing 4.8 grams of calcium nitrate, 2.5 grams of polyethylene glycol 200 and 4.5 grams of citric acid by an equal volume impregnation method, dried at 110°C for 4 hours and then calcined at 450°C for 6 hours to obtain a hydrorefining catalyst carrier;
[0082] 50 g of the above-mentioned carrier was mixed with a mixed solution containing phosphoric acid, nickel acetate and ammonium molybdate (equivalent to 3.2 g NiO, 13.4 g MoO3 and 2 g phosphoric acid) by an equal volume impregnation method, dried at 110°C for 6 hours and calcined at 450°C for 4 hours to obtain catalyst CAT-1.
[0083] Surface characteristics of catalyst CAT-1, with a specific surface area of 285m 2 / g, the average pore diameter is 13.5nm, and the pore volume is 0.85ml / g; there are weak acid sites and medium-strong acid sites on the surface of the hydrogenation catalyst, which has suitable surface acid properties, and the density ratio of weak acid sites to medium-strong acid sites is about 3.2:1.
[0084] Figure 1 This is the transmission electron microscope image of CAT-1. It can be seen that the active components of CAT-1 have a layered stacking structure with 3-7 layers and a stacking length of 3-8nm, showing very good dispersion. Figure 2 This is the ammonia temperature-programmed desorption (NH3-TPD) diagram of CAT-1. It can be seen that there are two types of acidic sites on the catalyst surface, weak acidic sites and medium-strong acidic sites, and the weak acidic sites and medium-strong acidic sites have an appropriate ratio, thus ensuring the high dispersion of metal active components.
[0085] 2. The above catalyst needs to be pre-sulfurized before use. The sulfurization conditions are as follows: maintain the low-nitrogen oil circulation of the sulfurized oil, the DMDS concentration in the sulfurized oil is 7000 mg / kg, the hydrogen partial pressure is 5.0 MPa, and the temperature is raised according to the program to stay at 230°C for 16 hours, 280°C for 16 hours and 320°C for 16 hours. The total sulfurization time is 48 hours.
[0086] 3. Hydrogenation refining reaction: the presulfurized catalyst and catalytic diesel (from the MIP process, containing 15-25% monocyclic aromatics, 50-60% dicyclic aromatics, and 2-8% tricyclic aromatics) are contacted with hydrogen for hydrogenation reaction;
[0087] The conditions are: reaction inlet temperature 280°C, reaction pressure 6.0 MPa, volume space velocity 1.0 h -1 , hydrogen to oil volume ratio is 1500, and the reaction results are shown in Table 1.
[0088] Example 2
[0089] Weigh 20 g of pseudo-boehmite equivalent to aluminum oxide, 130 g of aluminum oxide, and 8 g of sesbania powder, mix them, then add 20 g of polyvinyl alcohol solution (mass concentration of 5%), 2.4 g of 85% phosphoric acid, 3.2 g of 67% nitric acid, and 200 ml of water, and squeeze into The millimeter clover strips were dried at 110°C for 6 hours and then calcined at 700°C for 6 hours to obtain a carrier. 50 grams of the sample obtained by calcination was impregnated and mixed with a mixed aqueous solution containing 2.4 grams of calcium nitrate, 2.5 grams of polyethylene glycol 200 and 4.5 grams of citric acid by an equal volume impregnation method, dried at 110°C for 4 hours and then calcined at 450°C for 6 hours to obtain a hydrorefining catalyst carrier;
[0090] 50g of the above carrier was mixed with a mixed aqueous solution containing phosphoric acid, nickel acetate and ammonium molybdate (containing NiO3.2g, MoO313.4g, phosphoric acid 2g) by equal volume impregnation method, dried at 110℃ for 6 hours, and calcined at 450℃ for 4 hours to obtain catalyst CAT-2. The dispersion characteristics of catalyst CAT-2 are as follows: the specific surface area is 283m 2 / g, the average pore diameter is 13.5nm, and the pore volume is 0.85ml / g; there are weak acid sites and medium-strong acid sites on the surface of the hydrogenation catalyst, and the density ratio of the weak acid sites to the medium-strong acid sites is about 2.4:1. Figure 3 This is the transmission electron microscope image of CAT-1. It can be seen that the active components on the catalyst surface are in a layered stacking structure with 3-7 layers and a stacking length of 6-12nm.
[0091] The reaction conditions of the hydrotreating catalyst and the catalyst presulfiding conditions are the same as those in Example 1. The reaction results are shown in Table 1.
[0092] Example 3
[0093] Weigh 20 g of pseudo-boehmite equivalent to aluminum oxide, 130 g of aluminum oxide, and 8 g of sesbania powder, mix them, then add 20 g of polyvinyl alcohol solution (mass concentration of 5%), 2.4 g of 85% phosphoric acid, 3.2 g of 67% nitric acid, and 200 ml of water, and squeeze into The millimeter clover strips were dried at 110°C for 6 hours and then calcined at 700°C for 6 hours to obtain a carrier. 50 grams of the sample obtained by calcination was impregnated and mixed with a mixed aqueous solution containing 4.8 grams of calcium nitrate, 2.5 grams of polyethylene glycol 200 and 2.0 grams of citric acid by an equal volume impregnation method, dried at 110°C for 4 hours and then calcined at 450°C for 6 hours to obtain a hydrorefining catalyst carrier;
[0094] 50 g of the above-mentioned carrier was mixed with a mixed aqueous solution containing phosphoric acid, nickel acetate and ammonium molybdate (containing NiO3.2 g, MoO313.4 g, phosphoric acid 2 g) by equal volume impregnation method, dried at 110°C for 6 hours, and calcined at 450°C for 4 hours to obtain catalyst CAT-3. The dispersibility characteristics of catalyst CAT-3 are as follows: the specific surface area is 282 m 2 / g, the average pore size is 13.4nm, and the pore volume is 0.86ml / g; there are weak acid sites and medium-strong acid sites on the surface of the hydrogenation catalyst, and the density ratio of the weak acid sites to the medium-strong acid sites is about 3.2: 1. The active components on the catalyst surface have a layered stacking structure, the number of layers is between 3-10 layers, the stacking length is 6-18nm, and its dispersibility is further reduced.
[0095] The reaction conditions of the hydrotreating catalyst and the catalyst presulfiding conditions are the same as those in Example 1. The reaction results are shown in Table 1.
[0096] Example 4
[0097] Weigh 20 g of pseudo-boehmite equivalent to aluminum oxide, 130 g of aluminum oxide, and 8 g of sesbania powder, mix them, then add 20 g of polyvinyl alcohol solution (mass concentration of 5%), 2.4 g of 85% phosphoric acid, 3.2 g of 67% nitric acid, and 200 ml of water, and squeeze into The millimeter clover strips were dried at 110°C for 6 hours and then calcined at 700°C for 6 hours to obtain a carrier. 50 grams of the sample obtained by calcination was impregnated and mixed with a mixed aqueous solution containing 4.8 grams of calcium nitrate, 2.5 grams of Tween and 4.5 grams of citric acid by an equal volume impregnation method, dried at 110°C for 4 hours and then calcined at 450°C for 6 hours to obtain a hydrorefining catalyst carrier;
[0098] 50 g of the above-mentioned carrier was mixed with a mixed aqueous solution containing phosphoric acid, nickel acetate and ammonium molybdate (containing NiO3.2 g, MoO313.4 g, phosphoric acid 2 g) by equal volume impregnation method, dried at 110°C for 6 hours, and calcined at 450°C for 4 hours to obtain catalyst CAT-4. The dispersibility characteristics of catalyst CAT-4 are as follows: the specific surface area is 284 m 2 / g, an average pore diameter of 13.5nm, and a pore volume of 0.84ml / g; the density ratio of weak acid sites to medium-strong acid sites on the surface of the hydrogenation catalyst is about 3.0: 1. The active components on the catalyst surface present a layered stacking structure, with the number of layers ranging from 3 to 10 and a stacking length of 3 to 15nm.
[0099] The reaction conditions of the hydrotreating catalyst and the catalyst presulfiding conditions are the same as those in Example 1. The reaction results are shown in Table 1.
[0100] Example 5
[0101] Weigh 20 g of pseudo-boehmite equivalent to aluminum oxide, 130 g of aluminum oxide, and 8 g of sesbania powder, mix them, then add 20 g of polyvinyl alcohol solution (mass concentration of 5%), 2.4 g of 85% phosphoric acid, 3.2 g of 67% nitric acid, and 200 ml of water, and squeeze into The millimeter clover strips were dried at 110°C for 6 hours and then calcined at 700°C for 6 hours to obtain a carrier. 50 grams of the sample obtained by the calcination was impregnated and mixed with a mixed aqueous solution containing 5.2 grams of magnesium nitrate, 2.5 grams of polyethylene glycol 200 and 4.5 grams of citric acid by an equal volume impregnation method, dried at 110°C for 4 hours and then calcined at 450°C for 6 hours to obtain a hydrorefining catalyst carrier;
[0102] 50g of the above-mentioned carrier was mixed with a mixed aqueous solution containing phosphoric acid, nickel acetate and ammonium molybdate (containing NiO3.2g, MoO313.4g, phosphoric acid 2g) by equal volume impregnation method, dried at 110℃ for 6 hours, and calcined at 450℃ for 4 hours to obtain catalyst CAT-5. The dispersibility characteristics of catalyst CAT-5 are as follows: the specific surface area is 285m 2 / g, an average pore diameter of 13.4nm, and a pore volume of 0.84ml / g; the density ratio of weak acid sites to medium-strong acid sites on the surface of the hydrogenation catalyst is about 2.7: 1. The active components on the catalyst surface present a layered stacking structure, with 3-10 layers and a stacking length of 5-15nm.
[0103] The reaction conditions of the hydrotreating catalyst and the catalyst presulfiding conditions are the same as those in Example 1. The reaction results are shown in Table 1.
[0104] Example 6
[0105] Weigh the commercially available 150 g of clover-shaped gamma-alumina was dried at 110°C for 6 hours and then calcined at 700°C for 6 hours. 50 g of the sample obtained by calcination was impregnated and mixed with a mixed aqueous solution containing 4.8 g of calcium nitrate, 2.5 g of polyethylene glycol 200 and 4.5 g of citric acid by an equal volume impregnation method, dried at 110°C for 4 hours and then calcined at 450°C for 6 hours to obtain a hydrorefining catalyst carrier;
[0106] 50 g of the above-mentioned carrier was mixed with a mixed aqueous solution containing phosphoric acid, nickel acetate and ammonium molybdate (containing NiO3.2 g, MoO313.4 g, phosphoric acid 2 g) by equal volume impregnation method, dried at 110°C for 6 hours, and calcined at 450°C for 4 hours to obtain catalyst CAT-7. The dispersibility characteristics of catalyst CAT-7 are as follows: the specific surface area is 207 m 2 / g, the average pore size is 8.4nm, the pore volume is 0.7ml / g, and the density ratio of surface weak acid sites to strong acid sites is 1:1.2; the active components on the catalyst surface present a layered stacking structure with 3-10 layers and a stacking length of 6-25nm.
[0107] The reaction conditions of the hydrotreating catalyst and the catalyst presulfiding conditions are the same as those in Example 1. The reaction results are shown in Table 1.
[0108] Example 7
[0109] Weigh 20 g of pseudo-boehmite equivalent to aluminum oxide, 130 g of aluminum oxide, and 8 g of sesbania powder, mix them, then add 20 g of polyvinyl alcohol solution (mass concentration of 5%), 2.4 g of 85% phosphoric acid, 3.2 g of 67% nitric acid, and 200 ml of water, and squeeze into The clover strips of millimeters were dried at 110℃ for 6 hours and then calcined at 700℃ for 6 hours to obtain a carrier. 50 grams of the sample obtained by calcination was mixed with an aqueous solution containing 4.8 grams of calcium nitrate by an equal volume impregnation method, dried at 110℃ for 4 hours and then calcined at 450℃ for 6 hours to obtain a hydrorefining catalyst carrier;
[0110] 50g of the above-mentioned carrier was mixed with a mixed aqueous solution containing phosphoric acid, nickel acetate and ammonium molybdate (containing NiO3.2g, MoO313.4g, phosphoric acid 2g) by equal volume impregnation method, dried at 110℃ for 6 hours, and calcined at 450℃ for 4 hours to obtain catalyst CAT-9. The dispersibility characteristics of catalyst CAT-9 are as follows: the specific surface area is 284m 2 / g, an average pore diameter of 13.5nm, and a pore volume of 0.85ml / g; the density ratio of weak acid sites to medium-strong acid sites on the surface of the hydrogenation catalyst is about 3.2: 1. The active components on the catalyst surface present a layered stacking structure, with 3-10 layers and a stacking length of 5-25nm.
[0111] The reaction conditions of the hydrotreating catalyst and the catalyst presulfiding conditions are the same as those in Example 1. The reaction results are shown in Table 1.
[0112] Comparative Example 1
[0113] Weigh 20 g of pseudo-boehmite equivalent to aluminum oxide, 130 g of aluminum oxide, and 8 g of sesbania powder, mix them, then add 20 g of polyvinyl alcohol solution (mass concentration of 5%), 2.4 g of 85% phosphoric acid, 3.2 g of 67% nitric acid, and 200 ml of water, and squeeze into The millimeter clover strips were dried at 110°C for 6 hours and then calcined at 700°C for 6 hours to obtain a hydrorefining catalyst carrier;
[0114] 50 g of the above-mentioned carrier was mixed with a mixed aqueous solution containing phosphoric acid, nickel acetate and ammonium molybdate (containing NiO3.2 g, MoO313.4 g, phosphoric acid 2 g) by equal volume impregnation method, dried at 110°C for 6 hours, and calcined at 450°C for 4 hours to obtain catalyst CAT-D1. The dispersibility characteristics of catalyst CAT-D1 are as follows: the specific surface area is 280 m 2 / g, the average pore diameter is 13.5nm, and the pore volume is 0.84ml / g; the density ratio of weak acid sites to medium-strong acid sites on the surface of the hydrogenation catalyst is about 2.1:1. Figure 4 This is the transmission electron microscope image of CAT-1, and no obvious layered stacking structure can be seen.
[0115] The reaction conditions of the hydrotreating catalyst and the catalyst presulfiding conditions are the same as those in Example 1. The reaction results are shown in Table 1.
[0116] Comparative Example 2
[0117] Weigh 20 g of pseudo-boehmite equivalent to aluminum oxide, 130 g of aluminum oxide, and 8 g of sesbania powder, mix them, then add 20 g of polyvinyl alcohol solution (mass concentration of 5%), 2.4 g of 85% phosphoric acid, 3.2 g of 67% nitric acid, and 200 ml of water, and squeeze into The clover strips of millimeters were dried at 110℃ for 6 hours and then calcined at 700℃ for 6 hours to obtain a carrier. 50 grams of the sample obtained by calcination were impregnated and mixed with a mixed aqueous solution containing 2.5 grams of polyethylene glycol 200 and 4.5 grams of citric acid by an equal volume impregnation method, dried at 110℃ for 4 hours and then calcined at 450℃ for 6 hours to obtain a hydrorefining catalyst carrier;
[0118] 50 g of the above-mentioned carrier was mixed with a mixed aqueous solution containing phosphoric acid, nickel acetate and ammonium molybdate (containing NiO3.2 g, MoO313.4 g, phosphoric acid 2 g) by equal volume impregnation method, dried at 110°C for 6 hours, and calcined at 450°C for 4 hours to obtain catalyst CAT-D2. The dispersibility characteristics of catalyst CAT-D2 are as follows: the specific surface area is 283 m 2 / g, an average pore diameter of 13.4nm, and a pore volume of 0.85ml / g; the density ratio of weak acid sites to medium-strong acid sites on the surface of the hydrogenation catalyst is about 2.1: 1. The catalyst has no stacking structure.
[0119] The reaction conditions of the hydrotreating catalyst and the catalyst presulfiding conditions are the same as those in Example 1. The reaction results are shown in Table 1.
[0120] Comparative Example 3
[0121] Weigh 20 g of pseudo-boehmite equivalent to aluminum oxide, 130 g of aluminum oxide, and 8 g of sesbania powder, mix them, then add 20 g of polyvinyl alcohol solution (mass concentration of 5%), 2.4 g of 85% phosphoric acid, 3.2 g of 67% nitric acid, and 200 ml of water, and squeeze into The clover strips of millimeters were dried at 110°C for 6 hours and then calcined at 700°C for 6 hours to obtain a carrier. 50 grams of the sample obtained by calcination was impregnated and mixed with a mixed aqueous solution containing 4.8 grams of calcium nitrate, 2.5 grams of polyethylene glycol 200 and 3.0 grams of hydrochloric acid (36.5%) by an equal volume impregnation method, dried at 110°C for 4 hours and then calcined at 450°C for 6 hours to obtain a hydrorefining catalyst carrier;
[0122] 50g of the above-mentioned carrier was mixed with a mixed aqueous solution containing phosphoric acid, nickel acetate and ammonium molybdate (containing NiO3.2g, MoO313.4g, phosphoric acid 2g) by equal volume impregnation method, dried at 110℃ for 6 hours, and calcined at 450℃ for 4 hours to obtain catalyst CAT-D3. The dispersibility characteristics of catalyst CAT-D3 are as follows: the specific surface area is 257m 2 / g, an average pore diameter of 14.2nm, and a pore volume of 0.88ml / g; the density ratio of the weak acid sites to the medium-strong acid sites on the surface of the hydrogenation catalyst is about 1:1.3. The active components on the catalyst surface present a layered aggregate structure.
[0123] The reaction conditions of the hydrotreating catalyst and the catalyst presulfiding conditions are the same as those in Example 1. The reaction results are shown in Table 1.
[0124] Comparative Example 4
[0125] Weigh 20 g of pseudo-boehmite equivalent to aluminum oxide, 130 g of aluminum oxide, and 8 g of sesbania powder, mix them, then add 20 g of polyvinyl alcohol solution (mass concentration of 5%), 2.4 g of 85% phosphoric acid, 3.2 g of 67% nitric acid, and 200 ml of water, and squeeze into The millimeter clover strips were dried at 110°C for 6 hours and then calcined at 700°C for 6 hours to obtain a carrier. 50 grams of the sample obtained by the calcination was impregnated and mixed with a mixed aqueous solution containing 4.8 grams of calcium nitrate, 2.5 grams of polyethylene glycol 200 and 4.5 grams of citric acid by an equal volume impregnation method, dried at 110°C for 4 hours and then calcined at 450°C for 6 hours to obtain a hydrorefining catalyst carrier;
[0126] 50 g of the above carrier was mixed with a solution containing nickel acetate (containing 3.2 g of NiO) by an equal volume impregnation method, dried at 110°C for 6 hours, and calcined at 450°C for 4 hours to obtain catalyst CAT-6. The dispersion characteristics of catalyst CAT-6 are as follows: the specific surface area is 285 m 2 / g, an average pore diameter of 13.5nm, and a pore volume of 0.85ml / g; the density ratio of weak acid sites to medium-strong acid sites on the surface of the hydrogenation catalyst is about 3.2: 1. The active components on the catalyst surface are in a sheet-like structure with a length of 10-15nm.
[0127] The reaction conditions of the hydrotreating catalyst and the catalyst presulfiding conditions are the same as those in Example 1. The reaction results are shown in Table 1.
[0128] Table 1
[0129]
[0130]
[0131] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A hydrogenation catalyst, characterized in that The catalyst comprises a hydrogenation active component and a carrier, wherein the carrier comprises an alkaline earth metal, and the hydrogenation active component comprises a Group VIII element and a Group VIB element; the hydrogenation active component is in a layered stacking structure.
2. The hydrogenation catalyst according to claim 1, wherein The active components of the hydrogenation catalyst are in a layered stacking structure of 3-10 layers, and / or the stacking length of each layer is 3-25 nm; preferably, the active components of the hydrogenation catalyst are in a layered stacking structure of 3-7 layers, and / or the stacking length of each layer is 3-7 nm; and / or The carrier is selected from at least one of silicon aluminum molecular sieve, phosphorus aluminum molecular sieve, silicon dioxide, zirconium dioxide, titanium dioxide, and aluminum oxide; and / or The carrier comprises 0.1-1.0 wt % of an alkaline earth metal, preferably the alkaline earth metal is at least one selected from Mg, Ca, Sr and Ba, more preferably the alkaline earth metal is Ca; and / or The specific surface area of the hydrogenation catalyst is 150-300m 2 / g, preferably 180-300m 2 / g; and / or The average pore size of the hydrogenation catalyst is 10-20 nm, preferably 10-15 nm; and / or The pore volume of the hydrogenation catalyst is 0.7-1.3 ml / g, preferably 0.85-1.2 ml / g; and / or The density ratio of weak acid sites to medium-strong acid sites on the surface of the hydrogenation catalyst is 2-4:1; and / or In terms of weight percentage, in the hydrogenation catalyst, the carrier content is 50-85%, preferably 75-85%; the hydrogenation active component content is 15-50%, preferably 15-25%, calculated as metal oxide.
3. The hydrogenation catalyst according to claim 1 or 2, wherein The mass ratio of the Group VIII element to the Group VIB element in the hydrogenation active component measured in terms of metal oxides is 0.1-0.5; Preferably, The Group VIII element is at least one selected from Fe, Co, and Ni, preferably Ni and / or Co. The Group VIB element is at least one selected from Cr, Mo, and W, preferably Mo and / or W.
4. The method for preparing the hydrogenation catalyst according to any one of claims 1 to 3, characterized in that: The preparation method comprises: a. first mixing the carrier, the alkaline earth metal, the first additive and optionally the organic acid in a first solvent, first drying and first calcining to obtain an intermediate product; b. mixing the intermediate product with a hydrogenation active component precursor and a second additive in a second solvent, performing a second drying and a second calcination to obtain a hydrogenation catalyst; Among them, the first additive is a non-ionic surfactant; the second additive is a polybasic inorganic acid or a polybasic organic acid; preferably, the first additive is selected from polyethylene glycol and / or Tween; the second additive is a polybasic inorganic acid; more preferably, the first additive is polyethylene glycol 200; and the second additive is phosphoric acid.
5. The preparation method according to claim 4, wherein: The preparation method of the carrier comprises: mixing a carrier precursor, an extrusion aid and a peptizing acid to obtain the carrier; Preferably, The extrusion aid is selected from at least one of sesbania powder, polyvinyl alcohol and hydroxymethyl cellulose; and / or The peptizing acid is selected from at least one of phosphoric acid, nitric acid and acetic acid, and is preferably a mixed solution of nitric acid and phosphoric acid.
6. The preparation method according to claim 4 or 5, wherein: In step a, the weight ratio of the carrier, the alkaline earth metal in terms of oxide, the first additive and the organic acid is 1:0.01-0.04:0.02-0.05:0.05-0.15; and / or The organic acid is selected from at least one of citric acid, tartaric acid and oxalic acid; and / or The first solvent is selected from at least one of deionized water, ethanol, and acetic acid / sodium acetate buffer solution; and / or The second solvent is selected from at least one of deionized water, ethanol, and acetic acid / sodium acetate buffer solution.
7. The preparation method according to any one of claims 4 to 6, wherein: The first drying conditions include: drying temperature of 60°C-150°C, drying time of 2h-24h; and / or The first calcination conditions include: calcination temperature of 250° C.-750° C., calcination time of 2 h-12 h; and / or The second drying conditions include: drying temperature of 60°C-150°C, drying time of 2h-24h; and / or The second calcination conditions include: a calcination temperature of 250° C.-750° C. and a calcination time of 2 h-12 h.
8. Use of the catalyst according to any one of claims 1 to 3 in catalytic diesel hydrorefining.
9. A method for catalytic diesel hydrofining, characterized in that: The method comprises contacting catalytic diesel with hydrogen in the presence of a catalyst to perform a hydrogenation reaction; The catalyst is a presulfurized hydrogenation catalyst as claimed in any one of claims 1 to 3.
10. The method according to claim 9, wherein: The distillation range of the catalytic diesel is 200-370°C, preferably 200-330°C; and / or The density of the catalytic diesel is above 0.90 g / ml, preferably above 0.93 g / ml; and / or The catalytic diesel is from a DCC and / or MIP process. Preferably, the catalytic diesel contains, by weight percentage, 15-25% of monocyclic aromatic hydrocarbons, 50-60% of dicyclic aromatic hydrocarbons, and 2-8% of tricyclic aromatic hydrocarbons; and / or The conditions of the hydrogenation reaction include: reaction temperature 260-320°C, preferably 270-300°C; reaction pressure 5.0-8.0MPa, preferably 6.0-7.0MPa; volume space velocity 0.6-1.0h -1 , preferably 0.7-0.8h -1 ; Hydrogen to oil volume ratio 1000-2000, preferably 1200-1500; and / or The pre-sulfurization conditions include: under the conditions of hydrogen partial pressure of 4-6MPa and hydrogen sulfide concentration of 5000-15000ppm in circulating hydrogen, sulfurization at 210-250℃ for 12-20h, 260-300℃ for 12-20h and 310-340℃ for 12-20h according to programmed temperature increase; the total sulfurization time is 36-60h.
Citation Information
Patent Citations
Catalyst for hydrodesulfurization of hydrocarbons
CN1040610A
A combined method for catalytic diesel oil hydro-conversion and catalytic gasoline hydrogenation
CN105754646A
Method for preparing aromatic hydrocarbons from catalytic diesel oil through hydro-conversion
CN109777514A
Transformation technology for catalytic diesel
CN108624357A
Hydrofining catalyst and preparation method thereof
CN113976124A